Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Infection intensity and severity of Ranavirus transmission in juvenile wood frogs - Maya R. Rayle; Jesse L. Brunner; Nicole C. Dahrouge; Erin L. Keller; Tracy A. G. Rittenhouse (Oecologia, 2025)

Analyzing nitrogen dioxide to nitrogen oxide scaling factors for data-driven satellite-based emission estimation methods: A case study of Matimba/Medupi power stations in South Africa - Janne Hakkarainen; Gerrit Kuhlmann; Erik Koene; Diego Santaren; Sandro Meier; Maarten C. Krol; Bart J.H. van Stratum; Iolanda Ialongo; Frédéric Chevallier; Johanna Tamminen; Dominik Brunner; Grégoire Broquet (Atmospheric Pollution Research, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Metarhizium and Isaria as biological control agents against Meccus vector of Chagas disease - Conchita Toriello; Carolina Brunner-Mendoza; M. en C. Hortensia Navarro-Barranco; QFB Amelia Pérez-Mejía; Karla Murillo Alonso; M. en C. Berenice Jiménez-Santiago; M. en C Ana Cecilia Rodríguez-Pérez; Paz María Salazar-Schettino; Margarita Cabrera-Bravo (International Journal of Tropical Insect Science, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Metagenomic characterisation of bioaerosols during the dry season in Mexico City - M. C. Calderón-Ezquerro; N. Serrano-Silva; C. Brunner-Mendoza (Aerobiologia, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Seasonal dynamics and potential drivers of ranavirus epidemics in wood frog populations - Emily M. Hall; C. S. Goldberg; J. L. Brunner; E. J. Crespi (Oecologia, 2018)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Fine-root turnover rates of European forests revisited: an analysis of data from sequential coring and ingrowth cores - I. Brunner; M. R. Bakker; R. G. Björk; Y. Hirano; M. Lukac; X. Aranda; I. Børja; T. D. Eldhuset; H. S. Helmisaari; C. Jourdan; B. Konôpka; B. C. López; et al. (Plant and Soil, 2013)

Sarcopenia in the aging high-fat fed rat: a pilot study for modeling sarcopenic obesity in rodents - L. Cornelius Bollheimer; Roland Buettner; Georg Pongratz; Rita Brunner-Ploss; Christine Hechtl; Miriam Banas; Katrin Singler; Okka W. Hamer; Christian Stroszczynski; Cornel C. Sieber; Claudia Fellner (Biogerontology, 2012)

Migration patterns and changes in population biology associated with the worldwide spread of the oilseed rape pathogen Leptosphaeria maculans - A. DILMAGHANI; P. GLADIEUX; L. GOUT; T. GIRAUD; P. C. BRUNNER; A. STACHOWIAK; M.‐H. BALESDENT; T. ROUXEL (Molecular Ecology, 2012)
Pathogen introductions into novel areas can lead to the emergence of new fungal diseases of plants. Understanding the origin, introduction pathways, possible changes in reproductive system and population size of fungal pathogens is essential in devising an integrated strategy for the control of these diseases. We used minisatellite markers to infer the worldwide invasion history of the fungal plant pathogen Leptosphaeria maculans , which causes stem canker (blackleg) of oilseed and vegetable brassicas. Clustering analyses partitioned genotypes into distinct populations corresponding to major geographic regions, along with two differentiated populations in Western Canada. Comparison of invasion scenarios using Approximate Bayesian Computation suggested an origin of the pathogen in the USA, the region where epidemics were first recorded, and independent introductions from there over the last few decades into Eastern Canada (Ontario), Europe and Australia. The population in Western Canada appeared to be founded from a source in Ontario and the population in Chile resulted from an admixture between multiple sources. A bottleneck was inferred for the introduction into Western Canada but not into Europe, Ontario or Australia. Clonality appeared high in Western Canada, possibly because environmental conditions there were less conducive to sexual reproduction. Leptosphaeria maculans is a model invasive pathogen with contrasting features in different regions: shallow population structure, high genetic variability and regular sexual recombination in some regions, by comparison with reduced genetic variability, high rates of asexual multiplication, strong population structure or admixture in others.

Frequency of mutations associated with fungicide resistance and population structure of Mycosphaerella graminicola in Tunisia - Sameh Boukef; Bruce A. McDonald; Amor Yahyaoui; Salah Rezgui; Patrick C. Brunner (European Journal of Plant Pathology, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Strong Attraction of the Parasitoid Cotesia marginiventris Towards Minor Volatile Compounds of Maize - Marco D’Alessandro; Virginie Brunner; Georg von Mérey; Ted C. J. Turlings (Journal of Chemical Ecology, 2009)

Insecticide toxicity to Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) females and effect on descendant generation - Ulysses R. Vianna; Dirceu Pratissoli; José C. Zanuncio; Eraldo R. Lima; Jay Brunner; Fabrício F. Pereira; José E. Serrão (Ecotoxicology, 2009)

Toward understanding the human dimensions of the rapidly changing arctic system: insights and approaches from five HARC projects - Henry P. Huntington; Lawrence C. Hamilton; Craig Nicolson; Ronald Brunner; Amanda Lynch; Astrid E. J. Ogilvie; Alexey Voinov (Regional Environmental Change, 2007)

Specific root length as an indicator of environmental change - I. Ostonen; Ü. Püttsepp; C Biel; O. Alberton; M. R. Bakker; K. Lõhmus; H. Majdi; D. Metcalfe; A. F. M. Olsthoorn; A. Pronk; E. Vanguelova; M. Weih; et al. (Plant Biosystems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A novel locus for autosomal recessive nonsyndromic hearing impairment, DFNB63, maps to chromosome 11q13.2–q13.4 - E. Kalay; R. Caylan; A. F. Kıroglu; T. Yasar; R. W. J. Collin; J. G. A. M. Heister; J. Oostrik; C. W. R. J. Cremers; H. G. Brunner; A. Karaguzel; H. Kremer (Journal of Molecular Medicine, 2007)

Alcohol-inducible gene expression in transgenic Populus - S. A. Filichkin; R. Meilan; V. B. Busov; C. Ma; A. M. Brunner; S. H. Strauss (Plant Cell Reports, 2006)

A novel D458V mutation in the SANS PDZ binding motif causes atypical Usher syndrome - E. Kalay; A. P. M. de Brouwer; R. Caylan; S. B. Nabuurs; B. Wollnik; A. Karaguzel; J. G. A. M. Heister; H. Erdol; F. P. M. Cremers; C. W. R. J. Cremers; H. G. Brunner; H. Kremer (Journal of Molecular Medicine, 2005)

Molecular markers reveal extensive intraspecific below‐ground overlap of silver fir fine roots - I. BRUNNER; M. RUF; P. LÜSCHER; C. SPERISEN (Molecular Ecology, 2004)
Fine roots are expected to be important determinants of plant competition, but very little is known about the extent of root system overlap. Here, we describe the application of two highly variable plastide microsatellites to study the fine root distribution of tree individuals in a silver fir forest. We demonstrate that the spread of fine roots exceeds the width of above‐ground parts, and that fine root overlaps among neighbouring trees are extensive both laterally and in depth. This approach will help to improve models of below‐ground competition and will facilitate estimations of fine root biomass and thus of below‐ground C pools.

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Astrocytes protect the CNS: antigen-specific T helper cell responses are inhibited by astrocyte-induced upregulation of CTLA-4 (CD152) - Ulrike Gimsa; Anita ren; Pushpa Pandiyan; Daniela Teichmann; Ingo Bechmann; Robert Nitsch; Monika C. Brunner-Weinzierl (Journal of Molecular Medicine, 2004)

Experimental oral transmission of largemouth bass virus - J E Woodland; C J Brunner; A D Noyes; J M Grizzle (Journal of Fish Diseases, 2002)
Largemouth bass virus (LMBV) is a recently discovered iridovirus that causes a fatal disease of largemouth bass, Micropterus salmoides (Lacepède). Fish can become infected by waterborne LMBV, but oral transmission of this virus has not been demonstrated previously. Largemouth bass were gavaged with guppies, Poecilia reticulata Peters, which had been injected with LMBV, and then sampled periodically during a 7‐week observation period. The dose of LMBV averaged 10 5.6 tissue culture infectious doses – 50% cytopathic endpoint (TCID 50 ) per largemouth bass. Five of 24 largemouth bass exposed to LMBV became infected with the virus, but none of the fish had clinical signs typical of LMBV disease. Virus titres in largemouth bass were highest in swim bladder (10 5.5–9.5 TCID 50 g −1 ) and were 10 5.2 TCID 50 g −1 or lower in cutaneous mucus, head kidney, trunk kidney, spleen, gonad and intestine. These results indicate that LMBV can be transmitted orally to largemouth bass, but further study is needed to determine the factors affecting pathogenicity of the virus.

Identification of the N-acetyl-D-glucosamine-inducible element in the promoter of the Trichoderma atroviride nag1 gene encoding N-acetyl-glucosaminidase - C. Peterbauer; K. Brunner; R. Mach; C. Kubicek (Molecular Genetics and Genomics, 2002)

A Case of Lung Transplantation Following Mycoplasma pneumoniae Infection - F. Daxböck; G. Brunner; H. Popper; R. Krause; K. Schmid; G. Krejs; C. Wenisch (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Molecular identification of fine roots of trees from the Alps: reliable and fast DNA extraction and PCR–RFLP analyses of plastid DNA - I. Brunner; S. Brodbeck; U. BÜchler; C. Sperisen (Molecular Ecology, 2001)
Fine roots of trees are intensively used as indicators to assess soil alterations, e.g. those owing to atmospheric inputs of acidifying substances, but their identification to species with morphological criteria is difficult. In this study, we established molecular techniques in order to identify fine roots of the 30 most common tree species of the Alps. We developed a protocol for efficient isolation of DNA from fine roots with extraction of DNA in the presence of polyvinylpyrrolidone (PVP) and polyvinylpolypyrrolidone (PVPP). The trn L (UAA) intron of plastid DNA was used as a marker for fine root identification. We amplified and sequenced this intron with plant universal primers. The size of the sequences ranged from 444 to 672 bp . A synoptic key for species identification was designed on the basis of restriction fragment patterns predicted from sequence data. Using the restriction enzyme Taq I as key enzyme, and where necessary Hin fI, Rsa I and Cfo I, 16 taxa, including Picea abies , Larix decidua , Abies alba , and Fagus sylvatica , the dominant tree species of the Alpine region could be identified by agarose gel electrophoresis of restriction fragments. Fourteen taxa could be identified to the genus level, among them Quercus , Salix and Populus species. In a field study, conducted in a 20 × 30 m plot of a mixed forest with five tree species, fine roots of 43 out of 46 samples were identified and their distributions were mapped. These results demonstrate the utility of our DNA extraction method and of the trn L intron for the identification of fine tree roots.

Molecular mapping of the Rph7.g leaf rust resistance gene in barley (Hordeum vulgare L.) - S. Brunner; B. Keller; C. Feuillet (Theoretical and Applied Genetics, 2000)

Light-regulated transcription of a cryptochrome gene in the green algaMougeotia scalaris - K. D. Brunner; C. Zrb; H. . Kolukisaoglu; G. Wagner (Protoplasma, 2000)

High 5HT 2A receptor occupancy in M100907-treated schizophrenic patients - M. Talvik-Lotfi; S. Nyberg; A. -L. Nordström; H. Ito; C. Halldin; F. Brunner; L. Farde (Psychopharmacology, 2000)

Do assemblages of Coregonus (Teleostei: Salmoniformes) in the Central Alpine region of Europe represent species flocks? - M. R. Douglas; P. C. Brunner; L. Bernatchez (Molecular Ecology, 1999)
To examine models of evolution for Coregonus from the Central Alpine region of Europe, 20 populations from nine lakes were assessed for variation at six microsatellite DNA loci. Patterns of variation were tested against three evolutionary models: phenotypic plasticity, multiple invasions of lakes by divergent forms, and within‐lake radiation of species flocks. All sympatric and all but one allopatric pairs of populations were significantly divergent in allele frequencies. Pairwise F ‐statistics indicated reduced gene flow among phenotypically divergent sympatric populations. These results reject the hypothesis that within‐lake morphological and ecological diversity reflects phenotypic plasticity within a single gene pool. Genetic similarity was higher among forms within lakes than between populations of the same form in different lakes. Among‐lake divergence was primarily a product of allele size differences. Mantel tests contrasting patterns of genetic divergence against patterns predicted from the multiple invasions and species flocks models indicated that the latter is the best explanation of the observed genetic variation. Thus, reproductively isolated species diverged within lakes, with similar patterns repeatedly emerging among lakes. While this study argues for a particular mode of evolution in Central Alpine Coregonus , the taxonomy of these forms remains unresolved.

Microsatellite and mitochondrial DNA assessment of population structure and stocking effects in Arctic charr Salvelinus alpinus (Teleostei: Salmonidae) from central Alpine lakes - P. C. BRUNNER; M. R. DOUGLAS; L. BERNATCHEZ (Molecular Ecology, 1998)
Despite geographical isolation and widespread phenotypic polymorphism, previous population genetic studies of Arctic charr, Salvelinus alpinus , have detected low levels of intra‐ and interpopulation variation. In this study, two approaches were used to test the generality of low genetic diversity among 15 Arctic charr populations from three major drainages of the central Alpine region of Europe. First, a representative subsample of each drainage was screened by PCR–RFLP analysis of mtDNA using 31 restriction enzymes. All individuals but one shared an identical haplotype. In contrast, microsatellite DNA variation revealed high levels of genetic diversity within and among populations. The number of alleles per locus ranged from six to 49, resulting in an overall expected heterozygosity from 0.72 ± 0.09 to 0.87 ± 0.04 depending on the locus. Despite evidence for fish transfers among Alpine charr populations over centuries, genetic diversity was substantially structured, as revealed by hierarchical Φ statistics. Eighteen per cent of total genetic variance was apportioned to substructuring among Rhône, Rhine, and Danube river systems, whereas 19% was due to partitioning among populations within each drainage. Cluster analyses corroborated these results by drainage‐specific grouping of nonstocked populations, but also revealed damaging effects of stocking practices in others. However, these results suggest that long‐term stocking practices did not generally alter natural genetic partitioning, and stress the importance of considering genetic diversity of Arctic charr in the Alpine region for sound management. The results also refute the general view of Arctic charr being a genetically depauperate species and show the potential usefulness of microsatellite DNAs in addressing evolutionary and conservation issues in this species.